2018
DOI: 10.1002/clen.201700617
|View full text |Cite
|
Sign up to set email alerts
|

Determination of EC50Values for Cu, Zn, and Cr on Microorganisms Activity in a Mediterranean Sandy Soil

Abstract: Ecotoxicity of three potentially toxic metals (PTM) (Cu, Zn, and Cr) in a slightly acidic sandy soil is tested using the soil respiration test (OECD‐217) in order to determine EC50 values for the carbon transformation activity of microorganisms. Addition of an organic amendment of Populus leaves is also crossed with metal spiking in order to investigate possible interaction with metal toxicity. Soil respiration is measured at day 1 and 28 after the soil spiking with the PTM to assess short‐term effects on soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
(78 reference statements)
1
5
0
1
Order By: Relevance
“…This result indicates that these tests could be the most sensitive ones for the available PTEs concentration and properties in this soil. Others studies have performed the soil respiration test (OECD TG 217) and applied organic amendments or used soils with high organic matter contents but detected no toxic effects, not even at high metal concentrations [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates that these tests could be the most sensitive ones for the available PTEs concentration and properties in this soil. Others studies have performed the soil respiration test (OECD TG 217) and applied organic amendments or used soils with high organic matter contents but detected no toxic effects, not even at high metal concentrations [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing heavy metals and metalloids contents can have a negative effect on the C mineralization rate, as determined by respirometry techniques, and also on N transformation [ 2 , 17 , 18 ]. However, some studies have applied heavy metal in soils with high organic matter contents and found no toxic effect after adding these elements [ 19 ]. Obviously, there are also potential associated effects at high nutrient levels.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of migration of PTM in the system “industrial waste‒soil” have been studied in many publications. [ 2,3 ] The authors of papers on assessing quality of the environment [ 6–8 ] showed that the presence and high concentrations of copper and zinc ions in ES and their diverse mobility in the environment make these metals to be considered as sensitive indicators of industrial pollution. The level of soil contamination could be determined by the following indicators: enrichment factor, pollution load index, [ 2 ] geoaccumulation index, [ 3 ] contamination factor, and ecological risk index.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Ecotoxicity of Cu and Zn can be tested using the soil respiration test, in order to determine the carbon transformation activity of microorganisms. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Además, se ha encontrado que afectan los perfiles genéticos de las comunidades microbianas del suelo, alterando los genes de resistencia a metales , y reduciendo la actividad de las enzimas βglucosidasa, ureasa y fosfatasa ácida y alcalina afectando la degradación de nutrientes (Quiceno-Vallejo et al, 2020). La toxicidad del DAM está relacionada con la concentración de metales como Fe, Zn y Cu los cuales pueden interferir con la división celular, generando estrés oxidativo e inhibiendo el transporte de nutrientes esenciales (Carabassa et al, 2019) La red internacional para la prevención de drenajes ácidos estimó que cerca de 100.000 sitios mineros en varios países (USA, Australia, Reino Unido, Alemania, Perú y Chile) generan drenajes ácidos que afectan a más de 80.000 km de riberas de ríos y lagos con metales como Cd 2+ , Cu 2+ , Ag 1+ , Zn 2+ y As (III/V) (INAP, 2020). Además, a nivel mundial se producen más de 7.300 millones de toneladas de carbón mineral con presencia de DAM en todos los escenarios (WCA, 2020).…”
Section: Introductionunclassified